Engaging the religiocultural quest in development: An African indigenous perspective - Amenga-Etego, Rose Mary (HTS teologiese studies, 2016)
The intertwining nature of African life and livelihood is a considerable challenge to the discourse of development. In as much as the view on unlocking both the spiritual and physical dimensions of life in developmental endeavours is frowned upon, contemporary exploration into indigenous knowledge systems as an alternative discourse of development does not simply transform the dialogue but posits it as a discourse of power. This article examines the interplay between indigenous beliefs and knowledge systems and the discourse of development, with a focus on the Nankani in the Upper East Region of Ghana.